PENGETAHUAN WANITA MENOPAUSE TENTANG OSTEOPOROSIS DI DESA RAMBAH KECAMATAN RAMBAH HILIR - Sulistiawati, Wiwin; Nurmawilis, Nova; Nasriyah, Isom; Herlinovia (Jannatul Makwa Health : Jurnal Ilmiah Kesehatan (Scientific Journal of Health), 2026)
Osteoporosis is a disorder during menopause in women, this is due to a decrease and loss of bone mineral levels which can result in fractures and disability. Menopausal women experience osteoporosis more than men of the same age, having a 4 times higher risk of this happening is a decrease in estrogen hormone levels. The purpose of this study was to determine the knowledge of menopausal women about Osteoporosis in Rambah Village, Rambah Hilir District. Design This study uses a descriptive description presented using a frequency distribution table and the percentage of each characteristic. The sample in this study were women entering the menopause phase as many as 51 respondents. The research instrument used a questionnaire. The majority of respondents' knowledge in this study was Less as many as 22 people (43.13%), sufficient as many as 12 people (23.52%), and good as many as 17 people (33.33%). with respondents Respondents with knowledge Less based on the highest level of education from junior high school as many as 17 people (33.3%), The most common source of information obtained from electronic media as many as 22 people43.13%) and seen from the Activeness of Posyandu as many as 43 People (84.31%). Menopausal women are expected to be able to know about Osteoporosis during menopause. And it is hoped that the Rambah Village will collaborate with local health workers to provide more counseling and health information about Osteoporosis to mothers during menopause. The conclusion of this study is that the knowledge of menopausal women about Osteoporosis is mostly lacking. Keywords : Knowledge, Menopausal Women, Osteoporosis